Solvência fiscal de longo prazo dos regimes próprios de previdência dos estados e municípios - Marcelo Abi-Ramia Caetano (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– This article diagnosis the long run sustainability of the pension scheme for public employees (RPPS) in Brazilian subnational governments. The paper describes the rules applied to RPPS related to eligibility criteria, benefit formula, pension indexation, contribution rates and funding. The paper compares Brazilian RPPS against international standards and presents the actuarial deficits of states. Finally, it estimates fiscal impacts of different reforms. One can conclude that even ambitious reforms with high political cost are not able to eliminate the deficit, but they make its path more manageable.
Keywords: H75; H72; J45; 330; public employees pension scheme; fiscal sustainability of subnational governments; long-run forecasts for pensions